Is left bundle branch block pattern on the ECG caused by variable ventricular activation sequence? - Riedlbauchová, Lucie; Adla, Theodor; Suchánek, Vojtěch; Ložek, Miroslav; Tomis, Jan; Hozman, Jiří; Tomek, Viktor; Veselka, Josef; Janoušek, Jan (Pacing and clinical electrophysiology, 2020)
BACKGROUND: The presence and extent of ventricular dyssynchrony are currently assessed from the QRS complex morphology and width. However, similar electrocardiography (ECG) pattern may be caused by variable ventricular activation sequence. This may then contribute to interindividually different response to cardiac resynchronization therapy (CRT). METHODS: Electroanatomical mapping and magnetic resonance imaging scan were performed in 11 patients with left bundle branch block (LBBB, QRS 170 ± 14 ms) and heart failure of ischemic (coronary artery disease (CAD), n = 2) and nonischemic (dilated cardiomyopathy (DCM), n = 9) etiology. Ventricular activation sequence was studied during LBBB and final CRT programming. Presence and extent of scarring were analyzed in the 17-segment left-ventricular (LV) model. RESULTS: Regardless of etiology, presence of typical LBBB was associated with diffuse prolongation of impulse conduction with right-to-left activation sequence. Basal lateral wall was constant site of late activation. This activation pattern was present in "true LBBB," but also in LBBB-like pattern (persistent S wave in V5-6) and left axis deviation. Activation started in right vetricular (RV) apex in patients with left axis deviation at RV free wall in normal axis. Individuals with CAD and DCM patient displayed focal scar. Despite that they exhibited typical LBBB and activation sequence mirrored findings in other LBBB individuals. Reverse remodeling (∆LVESV > 15% after 6 months) was evident in 10 patients. CONCLUSIONS: Both typical LBBB and LBBB-like pattern might be associated with constant activation sequence regardless of etiology and scar localization. Activation initiation in RV apex, not LV activation sequence can be surrogate for left axis deviation. CRT caused inter- and intraventricular LV resynchronization without significantly changed RV activation sequence and duration.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Epicardial Mapping; Humans; srdeční resynchronizační terapie; Heart Failure; srdeční selhání; lidé středního věku; Electrocardiography; left bundle branch block; Female; Aged; senioři; lidé; Cardiac Resynchronization Therapy; electroanatomical mapping; ženské pohlaví; Male; Middle Aged; ECG; blokáda Tawarova raménka; Heart Ventricles; epikardiální mapování; resynchronization therapy; Bundle-Branch Block; mužské pohlaví; srdeční komory; biventricular pacing; elektrokardiografie